1992
DOI: 10.1128/jcm.30.8.2187-2190.1992
|View full text |Cite
|
Sign up to set email alerts
|

Further consideration of the clonal nature of Salmonella typhi: evaluation of molecular and clinical characteristics of strains from Indonesia and Peru

Abstract: We examined envelope protein profiles, chromosomal restriction endonuclease digest patterns, and immune responses to envelope proteins for collections of Salmonella typhi strains isolated in Peru and Indonesia. Only minor differences in envelope protein patterns were apparent among strains. Strains from 7 of 20 Indonesian patients had a distinct chromosomal digest pattern compared with patterns of Peruvian and other Indonesian strains. Strains with this pattern carried the gene for thej flagellar antigen (Hi-j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Few studies have been performed to determine if variations in clinical presentation are related to strain differences. Previous studies have, in fact, shown little correlation between strain characteristics and disease severity (6,8). This is perhaps not surprising, given the small number of strains studied and the well-known observation that S. typhi represents a single clone that has shown minimal intraspecies divergence in different parts of the world (14,16).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Few studies have been performed to determine if variations in clinical presentation are related to strain differences. Previous studies have, in fact, shown little correlation between strain characteristics and disease severity (6,8). This is perhaps not surprising, given the small number of strains studied and the well-known observation that S. typhi represents a single clone that has shown minimal intraspecies divergence in different parts of the world (14,16).…”
mentioning
confidence: 92%
“…No association between the characteristics of these clones and disease severity was found (8). Franco et al, utilizing envelope protein profiles, restriction fragment length polymorphism of chromosomal DNA, and immune response to envelope proteins, also found no clear correlation between strain characteristics and disease severity (6). A more recent study, however, reported an association between flagellar serotypes and decreased severity of illness and invasiveness (7).…”
mentioning
confidence: 99%
“…In contrast to these phenotypic approaches, genotypic techniques are believed to possess better reproducibility and discriminatory power (7). In a study of 69 S. typhi strains from Indonesia and Peru using envelope protein profiles, chromosomal restriction endonuclease digestion patterns, and immune response to envelope proteins, Franco et al (5) concluded that there are genotypic and phenotypic differences among S. typhi strains. Ribotyping studies of S. typhi isolates from different parts of the world, including those from the United States, Sicily, and Malaysia (1,9,11), have also indicated considerable genetic diversity.…”
mentioning
confidence: 99%
“…It is also important to emphasize that the phenotypic correlates of these genetic differences are unknown and the clinical significance of these genetic differences and their importance with regard to the virulence of individual strains remain to be evaluated. This remains as an important issue in research on typhoid fever in view of the observation that the reported clinical manifestations of typhoid fever differ markedly in different parts of the world (5,6), including Southeast Asia.…”
mentioning
confidence: 99%
“…More recently, there has been an increasing interest in the application of molecular techniques to type bacterial pathogens (35). With S. typhi, techniques such as multilocus enzyme electrophoresis (27,32), lipopolysaccharide (16) and envelope protein profiles (l1), chromosomal restriction endonuclease digestion patterns (11), and ribotyping (1, 24) have been used. Many of these techniques are not sufficiently sensitive for distinguishing individual strains and inves-tigators often find them tedious to perform.…”
mentioning
confidence: 99%